حدود المسؤولية الجزائية لعضو مجلس النواب العراقي في ضوء الحصانة النيابية - عاشور، أميل جبار (المركز الجامعي أفلو - معهد الحقوق والعلوم السياسية, 2020)
مما لا شك فيه أن حدود المسؤولية الجزائية للأعضاء المجالس النواب العراقي من الموضوعات المهمة في القانون الجنائي؛ وعليه توشك غالبية التشريعات الدستورية على منح أعضاء مجالس النواب نوعاً من الحصانة التي تمكن العضو النيابي من القيام بكافة أوجه مظاهر العمل النيابي بحرية تامة دون أن تلحقه أي نوع من المسؤولية، وبما أن تلك المسؤولية ومنها المسؤولية الجزائية تعد استثناء من القاعدة العامة التي توجب المساواة التامة بين المواطنين، فإنه يجب وضع الحدود القانونية للإطار الذي يجب أن تمارس فيه إطاره تلك الحرية، فلكي يتمكن أعضاء المجالس النواب العراقي من القيام بمهام عمله النيابي فلا بد من منحه الحصانة بشقيها الموضوعي والإجرائي التي تجنبه المسائلة عن أقوالة أثناء مناقشته وإقرار مشاريع القوانين داخل قبة البرلمانية، علاوة على ذلك قيامه بواجبة الرقابة على السلطة التنفيذية من خلال طرح الأسئلة والاستجوابية. كما أن من أهم إثار الحصانة هي إيقاف جميع الإجراءات الجنائية ولو بصورة موقتاً لحين أخذ إذن البرلمان، فضلاً عن ذلك تحول دون الاتهامات الكيدية ضد أعضاء البرلمان والتي تحول دون حضور النائب جلسات المجلس التي قد يمارسها النائب والتي تعد من مستلزمات الرقابة على إعمال السلطة التنفيذية.
Here is no doubt that the limits of the criminal responsibility of members of the Iraqi Council of Representatives are important issues in the criminal law; Consequently, most constitutional legislations are close to granting members of the Council of Representatives a kind of immunity that enables the member of parliament to carry out all aspects of the parliamentary work freely without inflicting any kind of responsibility on him, and since that responsibility, including criminal responsibility, is an exception from the general rule that requires complete equality Among citizens, the legal boundaries of the framework within which its framework must exercise that freedom must be established. In order for members of the Iraqi Council of Representatives to carry out the tasks of its Parliamentary work, it must be granted immunity, both substantive and procedural, that avoids accountability for statements during the discussion and approval of bills within the Parliamentary Dome Moreover, he has an obligation to monitor the executive authority by asking questions and interrogating, and one of the most important effects of immunity is the cessation of all criminal procedures, even temporarily until the permission of Parliament is taken, in addition to that prevent the malicious accusations against members of Parliament that prevent the presence of the deputy Council sessions that the deputy may practice, which are considered requirements for monitoring the implementation of the executive authority.
Keywords: الحصانة النيابية -- السلطات التنفيذية -- القوانين الجنائية -- التشريعات الدستورية -- المسؤولية الجزائية -- السياسة العراقية